2016
DOI: 10.1111/apha.12695
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus reuteri increases mucus thickness and ameliorates dextran sulphate sodium‐induced colitis in mice

Abstract: These results demonstrate that each of the two different L. reuteri strains, one human-derived and one-rat-derived, protects against colitis in mice. Mechanisms behind this protection could at least partly be explained by the increased mucus thickness as well as a tightened epithelium in the stem cell area of the crypts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
115
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 145 publications
(120 citation statements)
references
References 35 publications
5
115
0
Order By: Relevance
“…The colon houses trillions of commensal bacteria and allows a symbiotic relationship between host and microbes. We and others have identified a mucus layer that is firmly adhering to the epithelium in rats and mice in vivo, where it serves as a functional barrier . This firmly adherent mucus layer has also been shown by ex vivo measurements and histology of human colonic biopsies .…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…The colon houses trillions of commensal bacteria and allows a symbiotic relationship between host and microbes. We and others have identified a mucus layer that is firmly adhering to the epithelium in rats and mice in vivo, where it serves as a functional barrier . This firmly adherent mucus layer has also been shown by ex vivo measurements and histology of human colonic biopsies .…”
Section: Discussionsupporting
confidence: 54%
“…To maintain gut homeostasis, the majority of the microbiota should be kept at a distance from the epithelium, which is enabled by the bilayer of mucus . We were the first to describe this mucus bilayer, using an in vivo rat and mouse model developed in our laboratory . This model allows for studies of mucus thickness, dynamics, and regulation during health or inflammatory disease, as well as the impact of different diets .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Ahl et al [57] have demonstrated a reduction in colonic inflammation in C57Bl/6 mice using Lactobacillus reuteri R2LC and 5659. This study suggests that these two specific probiotic strains were also able to maintain a thicker, firmly adherent mucus layer compared to the control group.…”
Section: Resultsmentioning
confidence: 99%
“…The results of this previous report and the present study suggest that L. reuteri is an indigenous L. plantarum ‐SGB. Various healthy functional effects of L. reuteri have been reported in mice, such as anti‐inflammatory, anti‐allergic, hypocholesterolemic, and hypolipidemic effects (Ahl et al, ; Gao et al, ; Karimi e al., ; Lee et al, ; Taranto, Medici, Perdigon, Ruiz Holgado, & Valdez, ).…”
Section: Resultsmentioning
confidence: 99%
“…Dicksved et al () reported that selected L. reuteri strains maintain a functional mucosal barrier against mucus layer dysfunction following DSS treatment in Sprague‐Dawley rats. Furthermore, selected L. reuteri strains increased mucus thickness in a DSS‐induced model of colitis in C57BL/6 mice (Ahl, Liu, Schreider, Roos, Phillipson, & Holm, ). These reports suggest that oral administration of probiotics and functional compounds, including prebiotics, can inhibit lifestyle‐related and chronic diseases with the indigenous‐sensitive gut bacteria (SGB), such as L. reuteri , in mice.…”
Section: Introductionmentioning
confidence: 99%